2005
DOI: 10.1007/11550679_1
|View full text |Cite
|
Sign up to set email alerts
|

On the Revival of Dynamic Languages

Abstract: The programming languages of today are stuck in a deep rut that has developed over the past 50 years. Although we are faced with new challenges posed by enormous advances in hardware and internet technology, we continue to struggle with old-fashioned languages based on rigid, static, closed-world file-based views of programming. We argue the need for a new class of dynamic languages that support a view of programming as constant evolution of living and open software models. Such languages would require feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Despite the fact that other authors have already promoted dynamic languages as an instrument to improve flexibility (Ousterhout 1998;Nierstrasz et al 2005;Hirschi 2007), to the best of our knowledge no previous work has established precisely the relationships between the features of dynamic languages and the flexibility these languages provide.…”
Section: Final Remarks and Future Workmentioning
confidence: 89%
See 1 more Smart Citation
“…Despite the fact that other authors have already promoted dynamic languages as an instrument to improve flexibility (Ousterhout 1998;Nierstrasz et al 2005;Hirschi 2007), to the best of our knowledge no previous work has established precisely the relationships between the features of dynamic languages and the flexibility these languages provide.…”
Section: Final Remarks and Future Workmentioning
confidence: 89%
“…For example, Nierstrasz et al (2005) claim that most languages are static in the sense that they assume the world is consistent, but in reality most complex systems cannot be consistent, and they later suggest that dynamic languages can be a good solution to this problem. This line of reasoning is consistent with our claim that dynamic languages provide better Progressive Evaluation because they allow the system to run even when it is not entirely correct or consistent.…”
Section: Triangulation With Related Workmentioning
confidence: 97%
“…Self and Io) without bridging is another useful goal [17]. The Apple Newton showed that using a class-based language for models and a prototype-based language for views in the classic model-view-controller pattern is beneficial [20].…”
Section: Rationalementioning
confidence: 99%
“…In previous work we have argued that evolution is enabled by highlevel composition of components [2]. We have also argued that such systems should also be dynamic, they should support reflection on-demand, and they should provide mechanisms to manage the scope of change [33]. Change should be represented as a first-class entity, and both static and dynamic models of the running applications should be available at run-time to support continuous monitoring and analysis of evolution [34].…”
Section: Introductionmentioning
confidence: 99%